Lattice Monte Carlo and experimental analyses of the thermal conductivity of random-shaped cellular aluminum - Fiedler, Thomas (John Wiley & Sons Inc., 2009)
The effective thermal conductivity of open-and closed-cell aluminium foams with stochastic pore morphologies has been determined by numerical, analytical and experimental methods. A three dimensional analysis technique has been used where numerical calculation models are generated based on 3D computed tomographic (CT) reconstructions. The resulting three dimensional grid models are used for thermal Lattice Monte Carlo (LMC) analyses. The second part of this paper addresses experimental measurements of open-cell M-pore® and closed-cell Alporas® cellular aluminium. Finally, results obtained using both approaches are compared to classical analytic predictions.